KUALITAS BACA AL-QUR’AN ANAK: Penelitian Deskriptif Analitik di Desa Karyasari Kec. CibalongKab.Garut - Wiayanti, Euis Dewi; Mu’tamariah, Imas Musyaropah Ilham (THORIQOTUNA: Jurnal Pendidikan Islam, 2018)
Reading the Qur'an for Muslims is worship to Allah SWT. Forthat a child must be given understanding and familiarized to recite theQur'an from an early age. Reading the Qur'an does not give priority tothe absorption and understanding through the transfer of informationalone, but more priority on the development of ability. For that theability of learners need to be developed through active roles andexercises or activities that can support the ability to read Al-Qur'an. Inreading the Quran the quantity and quality go hand in hand. Which isthe best thing, all back to the condition of the child who read it. If thereading is good, of course the better for him is the quantity As for thechild who is not smooth, the best for him is the quality of reading theQur'an is still very minimal to find a quality child in reading the Quran.Many of the Muslims who read Al-Quran are not yet fluent, let aloneknow the correct rules of tajwid.